The Glucagon-Like Peptide-1 Analogue Liraglutide Reduces Seizures Susceptibility, Cognition Dysfunction and Neuronal Apoptosis in a Mouse Model of Dravet Syndrome - Liu, Shenhai; Jin, Zhe; Zhang, Yiling; Rong, ShiKuo; He, Wenxin; Sun, Kuisheng; Wan, Din; Huo, Junming; Xiao, Lifei; Li, Xinxiao; Ding, Na; Wang, Feng; et al. (Frontiers in Pharmacology, 2020)
Dravet syndrome (DS) is a refractory epilepsy typically caused by heterozygous mutations of the Scn1a gene, which encodes the voltage-gated sodium channel Nav1.1. Glucagon-like peptide-1 (GLP-1), an effective therapeutic agent for the treatment of diabetes, has recently become an attractive treatment modality for patients with nervous system disease; however, the relationship between GLP-1 analogue and DS remains unknown. This study aimed to determine the neuroprotective role of liraglutide in mouse and cell models of Scn1a KO-induced epilepsy. Epileptic susceptibility, behavioral changes, and behavioral seizures were assessed using electroencephalography (EEG), IntelliCage (TSE Systems, Bad Homburg, Germany), and the open field task. Morphological changes in brain tissues were observed using hematoxylin and eosin (HE) and Nissl staining. Expression of apoptosis-related proteins and the mammalian target of rapamycin (mTOR) signaling pathway were determined using immunofluorescence and western blotting in Scn1a KO-induced epileptic mice in vivo. Scn1a KO model cell proliferation was evaluated using the Cell Counting Kit-8 assay, and the effect of liraglutide on cellular apoptosis levels was examined using Annexin V-FITC/PI flow cytometry. Apoptotic signal proteins and mTOR were assessed using reverse transcription quantitative-polymerase chain reaction (RT-qPCR) and Western blotting, respectively, both at transcriptional and translational levels in vitro. Results showed that liraglutide significantly increased mRNA and protein expression of SCN1A in Scn1a KO-induced epileptic mice. In addition, liraglutide significantly alleviated electroencephalographic seizures, the severity of responses to epileptic seizures, and epileptic-related pathological changes in the brains of Scn1a KO-induced epileptic mice. Moreover, liraglutide protected against Scn1a KO-induced apoptosis, which was manifested in the phosphorylation of mTOR, as well as the downregulation of cleaved caspase-3 and restoration of the imbalance between BAX and BCL-2. In summary, findings of the present study suggest that liraglutide reduces seizure susceptibility and cognitive dysfunction in the mouse model of Dravet syndrome, and exerts anti-apoptotic and neuroprotective effects in Scn1a KO mice and cells.